Renaissance Motifs in Pictorial Art of Contemporary St. Petersburg Academists - Gracheva, Svetlana M. (Actual Problems of Theory and History of Art, 2016)
Academism has always been known as elite, idealistic, “pure” art oriented at the best traditions of world culture. Traditions of Renaissance art play a significant role in modern academic school of St. Petersburg, which carries a degree of refinement and seclusion from the experiments of so-called contemporary art. Particularly, the influence of Renaissance art is in the appeal to human, anthropomorphic, and humanistic orientation and the persistence of narrative painting. In this quest, there is a kind of desire of contemporary artists to realize their creative and human freedom. The article discusses the works of A. Mylnikov, H. Savkuev., Y. Kaljuta, O. Svederskaya, Yu. Behova, N. Ryzhikova, I. Korneev, and other St. Petersburg artists who appealed to the images of Renaissance art. Contemporary artists have a completely different cultural experience, and their worldview is not built literally on the ideas of Neoplatonism. Often the tradition of Renaissance culture is reviewed under the prism of many layers of other historical epochs. Contemporary academists find in the tradition only what is consonant with their personal experiences and feelings based on their modern professionalism and skill. It’s not just post-modernist citation of masterpieces, but the immersion into the mysteries and secrets of the craft and the desire to express their ideas through the tradition of Renaissance art.
Keywords: modern academism; St. Petersburg artists; Renaissance motifs; Academy of arts; traditions